PARA-PARA ADAT SEBAGAI LEMBAGA PERADILAN ADAT PADA MASYARAKAT HUKUM ADAT PORT NUMBAY DI KOTA JAYAPURA - SARA IDA MAGDALENA AWI (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
customarysettlementresolvedthroughthepara-para adat as judicial institution indigenouspeoples asPort Numbay hereacts as afacilitatorandmediatorin resolvingcriminalmattersand civilindigenouspeoples.Finesand penaltiesastraditionalinstruments andsettlementalternatives inindigenouscommunitiesand tribal peoplesPort Numbayin Jayapura, where settlementthroughcustomarylightersanctionthanupon completionvia thenational lawso thatindigenous peoplepreferNafriresolve the issuethroughtraditional institutionsthanthroughnational law. While theobstacles encountered in thejudicialsettlementthroughcustomaryPort Numbayissometimesa delaythe trialbecause ofthe absence ofone of the partiesto the disputethat isthe perpetrator, due to illness, theactordid notwantother people tointervene inproblem solving, as well as evidence ofthe witnesses andthe constraintsofvictims so thatcan complicatesettlementthroughcustomarycourt. It is suggested thatindigenousinstitutionsPort Numbayto be moreactively involved inefforts toresolve thecriminalcasecustomcase,given theindigenous peoplein the city ofJayapuraPort Numbaymore familiarway of resolving theproblem throughcustoms. Andto indigenousPort Numbayin Jayapurato alwayssupport the existence ofthe courtoragencyof indigenouspeoplesNafriin solvingthe problems oftraditionalcriminaland civilcustomsin order to achievethe securityandwelfare ofindigenous peoplesinPort Numbay.